The efficacy of red beetroot juice supplementation to improve cardiometabolic health in middle-aged/older adults with overweight or obesity - Litwin, Nicole S., author; Johnson, Sarah A., advisor; Pagliassotti, Michael J., committee member; Seals, Douglas R., committee member; Gentile, Christopher L., committee member; Rao, Sangeeta, committee member (Colorado State University. Libraries, 2019)
Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in developed societies worldwide. Advancing age is the primary risk factor for CVD, with lifestyle factors such as diet and nutrition also playing a role. Aging results in adverse changes to the arteries including vascular endothelial dysfunction which is characterized by a decline in nitric oxide (NO)-mediated endothelium-dependent dilation, and increased stiffening of large elastic arteries. This age-associated vascular dysfunction is predominantly driven by increased oxidative stress and chronic inflammation and contributes to the development of CVD through the development of atherosclerotic plaque and hypertension. Previous research suggests that a single high-fat meal may result in transient impairments in postprandial vascular endothelial function, which is thought to be driven by a postprandial pro-inflammatory and oxidative stress response to hypertriglyceridemia and/or hyperglycemia, resulting in a decline in NO bioavailability. This phenomenon may be exaggerated in aging individuals with overweight or obesity, though previous research findings have been inconclusive. Nonetheless, repeated high-fat meal consumption may increase CVD risk through impairments in postprandial vascular endothelial function, thus warranting further investigation. While the mechanisms of postprandial vascular endothelial dysfunction continue to be fully elucidated, an emerging area of research suggests that the oral microbiota may determine steady-state NO levels. Recent scientific discoveries indicate that the oral microbiota reduces dietary inorganic nitrate to nitrite and NO (known as the enterosalivary nitrate-nitrite-NO pathway), thus providing a new therapeutic target for CVD risk management. Red beetroot juice is a rich source of inorganic nitrate as well as other bioactive compounds such as betalains, flavonoids, carotenoids, and ascorbic acid, and previous research suggests that it may improve several parameters of cardiometabolic health including vascular endothelial function. The goals of this dissertation research were to 1) examine the clinical efficacy of acute and chronic red beetroot juice supplementation on postprandial vascular endothelial function after a high-fat meal challenge in middle-aged/older men and postmenopausal women with overweight or obesity, and 2) investigate the underlying mechanisms that contribute to vascular and metabolic responses to the meal challenge and supplementation, including the nitrate-dependent and -independent effects of red beetroot juice. To investigate the aforementioned, we conducted a randomized, double-blind, placebo-controlled, 4-period, crossover, clinical trial. To investigate the nitrate-dependent and -independent effects of red beetroot juice, we used 1) a placebo concentrate devoid of inorganic nitrate or polyphenols, 2) red beetroot juice concentrate, 2) nitrate-depleted red beetroot juice concentrate, and 4) a placebo concentrate with an equivalent dose of inorganic nitrate to that of red beetroot juice. We first examined the impact of acute and chronic red beetroot juice supplementation on postprandial vascular endothelial function and other cardiometabolic responses to a high-fat meal challenge. We found that the high-fat meal led to postprandial alterations in several cardiometabolic parameters but did not impair vascular endothelial function. Significant acute and chronic increases in saliva and plasma NO metabolites were observed following consumption of red beetroot juice and the placebo plus inorganic nitrate, but these increases were not paralleled by significant changes in vascular endothelial function. Although the meal and treatments altered several other parameters of cardiometabolic health, there were no consistent effects of the treatments on those parameters. Next, we examined the relationship between oral nitrate-reducing bacteria and NO metabolites following acute and chronic red beetroot juice supplementation to gain insight on the impact of the oral microbiota on dietary nitrate metabolism and vascular responses to the high-fat meal. We found that red beetroot juice and inorganic nitrate salt supplementation may alter the oral microbiome to favorably affect NO metabolism and vascular endothelial function in this population. Taken together, these results suggest that although red beetroot juice did not modulate postprandial vascular endothelial function, it may be a promising dietary intervention for targeting the enterosalivary nitrate-nitrite-NO pathway to increase NO bioavailability in middle-aged/older adults with overweight or obesity. Further research is needed to evaluate the potential of red beetroot juice as an oral microbiota targeted therapy for improving NO bioavailability and overall cardiovascular health. Additionally, further research is needed to better understand the impact of high-fat meal consumption on cardiometabolic health.